a) Simplify the expression and explain each step. (2 points)

4(3x + 2) – 2


b)  Factor the expression completely.  (1 point)


20b – 16





Respuesta :

a) 4 (3x+2)-2
12x+8-2
12x+6
2x+1 simplified expression

Answer:

a) [tex]4\left(3x+2\right)-2=12x+6[/tex]

b) [tex]20b-16= 4\left(5b-4\right)[/tex]

Step-by-step explanation:

a) To simplify the expression you must:

Expand [tex]4(3x + 2)[/tex]:

Apply the distributive law: [tex]\:a\left(b+c\right)=ab+ac[/tex]

[tex]a=4,\:b=3x,\:c=2\\\\4\left(3x+2\right)=4\cdot \:3x+4\cdot \:2[/tex]

Simplify [tex]4\cdot \:3x+4\cdot \:2= 12x+8[/tex]

[tex]12x+8-2[/tex]

Subtract the numbers: [tex]4\left(3x+2\right)-2=12x+6[/tex]

b) To factor the expression [tex]20b - 16[/tex] you must:

Rewrite 16 as [tex]4\cdot 4[/tex] and 20 as [tex]4\cdot 5[/tex]

[tex]20b-16=4\cdot \:5b-4\cdot \:4[/tex]

Factor out common term 4

[tex]20b-16= 4\left(5b-4\right)[/tex]